Lesser Poland Department in the Commission of National Education’s education system - Meissner, Andrzej; Pękowska, Marzena; Ślęczka, Ryszard (Instytut Historii Nauki im. Ludwika i Aleksandra Birkenmajerów Polskiej Akademii Nauk, 2018)
The Lesser Poland Department was created by the Commission of National Education in 1783. That year, the territorial organisation of the school network was established, department school authorities were appointed and teaching staff were employed. The Lesser Poland Department included the academic department school in Lublin, academic subdepartment schools in Kraków, Pińczów and Sandomierz and subdepartment schools run by religious orders in Kielce, Krasnystaw and Stężyca. This article is an attempt at characterising the educational facilities operating in the Lesser Poland Department and their organisational and educational issues with structural transformations, material base, teaching plans and programmes, textbooks, educational process and school inspections. Considerable attention was paid to the principles of youth education, school authorities, teachers and the student community. Efforts were also made to show the role of the presented facilities in local communities.
Keywords: Commission of National Education; Lesser Poland Department; school; teachers